Socioeconomic disparities in outdoor branded advertising in San Francisco and Oakland, California - Neha Zahid; Richard Pulvera; Kristine A. Madsen; Matthew M. Lee; Ana Ibarra-Castro; Jennifer Falbe (Preventive Medicine Reports, 2022)
Advertising exerts a powerful influence over consumer decision-making, and disproportionate marketing for unhealthy products may contribute to health inequities. The objective of this study was to examine socioeconomic and racial and ethnic disparities in outdoor branded advertising for products harmful to health in San Francisco and Oakland, CA. We collected cross-sectional data on outdoor advertising from 372 blocks with ≥ 1 residential or mixed-residential parcel in SF and Oakland in 2018–2019. Blocks were randomly sampled by city, land use, majority vs. non-majority Black and/or Hispanic composition, and upper and lower tertiles of household income. Advertisements were coded by product, healthfulness, and branding. Exposure variables were neighborhood household median income and percent of residents who were Hispanic of any race, non-Hispanic Asian, non-Hispanic Black, and non-Hispanic White. The primary outcome variable was block-level dichotomous presence of any unhealthy branded advertisement for food, beverage, alcohol, or tobacco. Analyses were unadjusted and adjusted for land use and number of total advertisements on each block. Each additional $10,000 in neighborhood household median income was associated with an 11% lower adjusted odds of having any unhealthy branded advertisements on the block (95%CI: 0.80–0.99; P = 0.03). There were no significant associations between neighborhood racial and ethnic composition and presence of unhealthy branded advertisements, but with each 10% higher neighborhood composition of Hispanic residents, there was a borderline significant higher presence of unhealthy branded advertisements (OR = 1.23; 95%CI: 1.00–1.51; P = 0.05). Results indicate that low-income neighborhoods were disproportionately exposed to outdoor branded advertisements for unhealthy products.